Propagación vegetativa por injertos en plukenetia volubilis l. empleando patrones interespecifico e intergenericos (Euphorbiaceae) en la provincia de San Martín - García Sánchez, Marco Antonio (2008)
In order to determine the effect of two techniques of grafting (stinger central and splicing) and four patterns (Plukenetia sp (Amazonas), Caryodendron orinocense, Jatropha curcas and Ricinus communis) on the ignition and growth in sacha grafts inchi (Plukenetia volubilis L.) under conditions of nursery, this experiment was conducted at the Research Institute of the Peruvian Amazon, located in the district of Morales, province and region of San Martin, during the period from June to October 2008. Used a design of randomized blocks in a split plot comprised of eight treatments, four repetitions and experimental units of ten grafted plants. The results show that there is no significant effect on the techniques of grafting on the percentage of ignition, rate of survival, number of outbreaks, number of leaves, length and diameter of the outbreak of the outbreak of the graft, but a significant effect on rates patterns in all variables. The largest percentage of ignition and sobrevinvencia shows the pattern of Plukenetia sp. (Amazonas) with values of 96.25% and 97.25% respectively. Also this pattern will be statistically distinguished from other types of patterns especially in the growth of graft in Sacha inchi (Plukenetia volubilis L.). We conclude that it is possible graft sacha inchi using the techniques and barbed central junction used as a pattern Plukenetia sp. (Amazonas) under greenhouse conditions.